Cross-border collaboration for neglected tropical disease efforts—Lessons learned from onchocerciasis control and elimination in the Mano River Union (West Africa). Issue 1 (December 2016) - Gustavsen, Kenneth; Sodahlon, Yao; Bush, Simon
Abstract Diseases don't respect borders, so efforts to control and eliminate diseases must also be flexible and adaptable enough to effectively reach the populations that live in the areas around national frontiers. Onchocerciasis, commonly known as river blindness is a tropical disease that has historically affected millions of people in 35 countries in Africa and Latin America. In Africa, programs and partnerships to address river blindness through mass drug administration have been active for more than 25 years. While in many cases the disease is found in isolated foci that fall entirely within national boundaries, the geographic scope of many affected areas crosses country borders. National river blindness programs are the responsibility of each nation's Ministry of Health, so in cross-border situations there is a need for effective country-country collaboration. Cross-border collaboration for onchocerciasis control efforts in the countries of the Mano River Basin illustrates the positive impact of a creative model, and offers lessons for expanded application for onchocerciasis elimination as well as other neglected tropical disease (NTD) control and elimination programs.